2001
DOI: 10.1177/089124301015004003
|View full text |Cite
|
Sign up to set email alerts
|

The Paradoxical Relationship Between Gender Inequality and Rape

Abstract: This article develops and tests a refined feminist theory of rape. The author proposes that the short-term effect of gender equality is an increased rape rate via increased threats to the status quo, whereas the long-term effect of gender equality is reduced rape rates via an improved social climate toward women. Using panel data for 109 U.S. cities over three decades—1970, 1980, and 1990—the author's expectations are generally confirmed. Because measures of inequality are used, supportive cross-sectional coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
156
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(165 citation statements)
references
References 12 publications
9
156
0
Order By: Relevance
“…This would be informed by the prediction (Russell 1975;Whaley 2001) that, over time, the backlash effects of greater gender parity found in other research might ultimately give way to an ameliorative effect upon female violent victimization as was found in this study. To illustrate, in the period of 1980 to 1988, the proportion of college students who are women increased by approximately three percent, from 51.4 percent to 53.7 percent.…”
Section: Discussionmentioning
confidence: 57%
“…This would be informed by the prediction (Russell 1975;Whaley 2001) that, over time, the backlash effects of greater gender parity found in other research might ultimately give way to an ameliorative effect upon female violent victimization as was found in this study. To illustrate, in the period of 1980 to 1988, the proportion of college students who are women increased by approximately three percent, from 51.4 percent to 53.7 percent.…”
Section: Discussionmentioning
confidence: 57%
“…This backlash hypothesis stressed an unintended consequence of female empowerment: increased gender equality represented a threat to male dominance and might result in higher rates of female victimization as males react defensively (Messerschmidt, 1993). This approach (Russell, 1975;Williams & Holmes, 1981) was similar to Blalock's threat hypothesis (1967) and also received some empirical support, with Bailey (1999), Brewer and Smith (1995), Vieraitis and Williams (2002), and Whaley (2001) showing a positive relationship between selected measures of gender equality and rape or female homicide victimization.…”
Section: Previous Literaturementioning
confidence: 84%
“…It was notable, as well, that the effects applied to Whites but not to overall rates, which might offer some limited support for the theories, though seemingly not through the mechanisms tested here. Whaley (2001) showed that the association between gender parity and female victimization might be positive in the short-term, but negative over longer periods. She concluded that the initial threat to malesT privileged status might result in an immediate backlash.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the backlash hypothesis predicts that women's gains relative to men will, at least in the short run, increase the female homicide victimization rate. As Whaley (2001) argues in her article on gender inequality and rape, these hypotheses are best tested by including time in the models. However, past research on gender equality and female homicide victimization has rarely included the element of time and often excludes measures of women's absolute status and therefore has not adequately addressed these three overlapping and theoretically significant hypotheses.…”
Section: Discussionmentioning
confidence: 99%